Dermatophytosis and STAT3 mutation. (17th September 2018) - Simpson, J.K.; Fröbel, P.; Seneviratne, S.L.; Brown, M.; Lowe, D.M.; Grimbacher, B.; Fliegauf, M.; Fearfield, L.
Summary: Dermatophytes are fungi that cause skin infections such as ringworm and athlete's foot. They are very unlikely to cause infection deeper inside the body in people with normal immunity. STAT3 (Signal Transducer and Activation of Transcription 3) mutations are genetic defects known to be associated with deep fungal infections. The authors, based in London and Freiburg, present a case report of a 45‐year old man of Indian descent who developed a mass in the groin associated with a widespread itchy rash. CT imaging showed that the groin mass extended into the abdomen. A biopsy of the groin mass showed extensive infiltration by the ringworm fungus Trichophyton interdigitale . Skin biopsy showed areas of ulceration with breakdown of collagen in the skin layer called the dermis, resembling that seen in so‐called perforating disorders, where damaged collagen fibres are spontaneously pushed through the skin. These changes, called pseudoperforation, can be seen with intense scratching. Deletion of the STAT3 gene was found in the patient's blood cells. The rash cleared and the groin mass reduced considerably after three months of oral antifungal treatment. The authors conclude that the unusual deep infection with this skin fungus was caused by the genetic abnormality and that the extensive rash was a reaction to this fungal infection. Abstract : Linked Article:  Simpson et al. Br J Dermatol 2018;179 :750–754